The Effect of Preservation Methods on the Nutritional Quality of Fluted Pumpkin (Tel/airia occidentalis) Leaves: Nutritional Quality of Fluted Pumpkin - Joseph Oboh, Fred Omon; Aigbe, Osayuwamen (Biological Sciences - PJSIR, 2011)
The present research was undertaken to investigate the effect of various blanching and drying treatments on the vitamin C, ?-carotene, iron, protein content and drying time of fluted pumpkin (Telfairia occidentalis Hook) leaves. The leaves were subjected to sun or oven drying alone or after blanching in boiling water, dilute citric acid (0.3%) or dilute potassium meta-bisulphite (0.5%). In the absence of blanching pre-treatment, oven drying resulted in shorter drying time for the leaves and a higher vitamin C content of the dried product than sun drying and there was no significant difference (p>0.01) between the protein, ?-carotene and iron content of the oven and sun dried products. Leaves blanched in boiling water, dilute citric acid, or dilute potassium meta-bisulphite solution, followed by sun or oven drying had less vitamin C, iron, protein and ?-carotene than leaves dried without blanching. Compared with the use of boiling water, blanching in boiling potassium meta-bisulphite reduced the loss of ?-carotene, protein and iron; blanching in dilute citric acid reduced the loss of iron. Except for citric acid pre-treatment, blanching prior to drying shortened drying time.